Strategic SWOT Analysis of Municipal Solid Waste Management and Waste Bank System in Bandung City; Toward a Circular and Sustainable Urban Future - Margaretha, Rita (Journal Governance Bureaucratic Review, 2025)
Bandung City faces escalating municipal solid waste challenges driven by rapid urban growth, consumption patterns, and limited treatment capacity. In response, waste banks (bank sampah) have emerged as community-based initiatives that promote recycling and waste segregation; however, their performance varies widely across districts due to institutional, financial, and technological constraints. This study aims to evaluate the strategic role of waste banks within Bandung’s municipal solid waste management system through a structured SWOT analysis. A descriptive qualitative approach was applied, utilizing secondary data from journal articles, government reports, and credible news sources published between 2015 and 2025. Findings reveal strong community participation, environmental awareness, and institutional support as core strengths, while weaknesses include inadequate infrastructure, inconsistent funding, and the absence of digital monitoring systems. Opportunities are found in circular economy policies, CSR-based partnerships, and technological innovations for data management. External threats include fluctuating recyclable prices, landfill capacity limitations, and policy instability. Based on these insights, strategic recommendations were formulated, including the integration of waste banks into formal municipal planning, digital platform adoption, standardized operating procedures, and cross-sector collaboration. The study concludes that waste banks hold significant potential to support Bandung’s transition toward a circular and sustainable urban waste-management model, provided that institutional strengthening and technological innovation are prioritized. This research serves as a practical reference for policymakers, academics, and community stakeholders in addressing urban waste challenges.